Controversia en materia fiscal sobre la inembargabilidad de bienes sociales dentro del procedimiento coactivo - Mendieta Carranza, Carolina Beatriz (2014)
This research aims to define the scope and application of Article 120 of the Tax Code concerning the exclusive third party property in the case that the assets of the conjugal partnership is affected by debts of only one spouse. The process of enforced collection by tax debts is governed by the tax code, and this legislation shouldn’t be applied ignoring other rules, such as the civil code that gives special protection to property rights, having established that social goods are unalienable, without But the Tax Administration mistakenly lock precautionary measures on corporate assets to the debt only one spouse. In this situation the debtor spouse intervention in accordance with Article 120 of the tax code, as excluding third property, in order to ensure the reversal of the seized property belonging to the conjugal partnership is needed, however the administration tax has rejected these requests, denying the legal nature of the conjugal partnership regime, in which the provisions of social goods must be authorized by both spouses or one of them to possess special power to perform such acts; or otherwise, expect a change of property regime or the demise of the regime of community of property